The Influence of Brand Awareness and Product Quality on Purchase Decisions (Case Study of Aqua Consumers in Klampis Village) - Nurdiyansyah, Wawan; Suryaniningsih, Suryaniningsih; Duladi, Duladi; Yunita, Ade (CV. Civiliza Publishing, 2025)
The sales of bottled drinking water (AMDK) in Indonesia have grown rapidly, increasing competition among brands. Aqua remains the dominant brand in Klampis Village. This study aims to examine the influence of brand awareness and product quality on consumer purchasing decisions, both partially and simultaneously. A quantitative approach was used with 97 respondents selected through purposive sampling. Data were collected through observation, interviews, and questionnaires, and analyzed using multiple linear regression. The t-test results show that brand awareness (t = 3.923; sig. 0.000) and product quality (t = 9.987; sig. 0.000) both have a significant positive effect on purchasing decisions. The F-test also indicates a significant simultaneous effect (F = 126.009; sig. 0.000). These findings conclude that both brand awareness and product quality significantly influence consumer purchasing decisions for Aqua in Klampis Village. It is recommended that Aqua strengthen its brand image and maintain product quality to encourage repeat purchases.